Estudo comaprativo da resistência da união esmalt/resina/metal. Efeito de resinas de fixação, artifícios retentivos e ligas metálicas. - Camparis Bussadori, C. M.; de Angelis Porto, C. L. (My University, 1990)
The purpose of this study was to compare the enamel/resin/metal bond tensile strength by using human canines, in which castings were bonded. These castings were obtained by Co-Cr or Ni-Cr alloys and showed four types of mechanisms of retention: 50 micrograms aluminum oxide abrasive, electrochemical etch, acrylic beads metal mesh. The castings were bonded utilizing Comspan Opaque and Panavia Ex. The specimens were subjected to tensile forces after 24 hours in an Instron machine. The castings subjected to 50 micrograms aluminum oxide abrasive and bonded utilizing Panavia EX showed the biggest bond tensile strength.
Comparative study of tensile strength of enamel/resin/metal interface. Effect of bonding resins, retention mechanisms and metal alloys
Keywords: aluminum oxide; chromium derivative; Panavia EX; phosphate; resin; canine tooth; cementation; comparative study; denture; human; instrumentation; materials testing; surface property; tensile strength; Aluminum Oxide; Chromium Alloys; Comparative Study; Cuspid; Dental Bonding; Denture, Partial, Fixed; English Abstract; Human; Materials Testing; Phosphates; Resins, Synthetic; Surface Properties; Tensile Strength